Effects of Cholestasis Induced by ANIT on Liver Function and Important Signaling Pathways in Rats - Thamer, Reham Hassan (American Journal of Biology and Natural Sciences, 2026)
This study was designed to study the effects of alpha-naphthyl isothiocyanate (ANIT) on vector liver function and histological changes in Wistar rats (focusing on biochemical markers and important signaling pathways related to cholestasis). Ten male rats were used and divided in two groups, a control group which received corn oil and an ANIT group that received ANIT orally at the dose of 100 mg/kg. Blood collection was performed after 48h to determine serum liver enzymes (ALT, AST, ALP, GGT), total bilirubin (TSB) and total bile acids (TBA). In addition, histopathological examination of liver sections stained with H&E was also performed for the evaluation of tissue injury.The results showed a significant increase in the levels of all parameters measured in ANIT group compared with the control. The results showed ALT level was increased from 26.80 +-1.10 to 47.02+-1.64 1.U/L and AST level was increased from 27.56+-2.40 to 55.07+-2.81 1.U/L. ALP level was increased from 100.68+-2.02 to 353.45+-36.37 1.U/L and GGT level was increased from 236.82+-14.83. These findings provide clear evidence that ANIT induces acute cholestasis that is associated with extensive hepatic injury. The biochemical and the histological changes support the authenticity of ANIT as an experimental model of cholestasis. This data set provides a basis for studying FXR, Nrf2 and AMPK signaling pathways for the design of future therapeutic strategies.